PERANCANGAN IKLAN LAYANAN MASYARAKAT KESEJAHTERAAN HEWAN PELIHARAAN - Apriani Apriani; Bobby Halim; Yosef Yulius (Besaung : Jurnal Seni Desain dan Budaya, 2018)
Dog pets are very much in demand by the race breeds Society. But dog keepers are less responsible to the dog and less responsive to what is needed by the dog. This will lead to neglect of existing dogs that lead to violence against dogs. Lack of education and information. Dog keepers do not know the important things related. The existence of this design greatly facilitates the dog keepers neglect their dogs in terms of physical and mental as well as provide education to dog keepers in the care of his dog. In addition, the Design of Public Service Animal Welfare Service is expected to overcome the problems of abandoned dogs. These public service advertisement media designs are created using the flat display design style to make it more attractive and modernKeyword:  Dog pets, Neglected Dog, Public service announcements